1985
DOI: 10.1111/j.1348-0421.1985.tb00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mutacin Administration on Streptococcus mutans‐Induced Dental Caries in Rats

Abstract: A bacteriocin from serotype c Streptococcus mutans strain C3603 was examined for its inhibitory effect on experimental dental caries in rats infected with S. mutans MT8148R (serotype c). Significant reduction in the incidence of dental caries was found only when bacteriocin was incorporated both in the drinking water and in the diet at a high concentration.However, caries reduction was not as great as expected and the addition of bacteriocin to drinking water alone had no effect on the recovery of S. mutans, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The nature of bacteriostatic substance may not be suitable for the application for the prevention of pneumococcal diseases, directly. Ooshima et al, reported that the mutacin, which was the bacteriocin produced by S. mutans, completely killed the cells grown in sucrose-free medium, whereas the bacteriocin did not kill the S. mutans cell grown in a sucrose-containing medium [17]. The inhibitory mechanism of the bacterioci-like substance in this study may be different from that of other known bacteriocins.…”
Section: Discussioncontrasting
confidence: 55%
“…The nature of bacteriostatic substance may not be suitable for the application for the prevention of pneumococcal diseases, directly. Ooshima et al, reported that the mutacin, which was the bacteriocin produced by S. mutans, completely killed the cells grown in sucrose-free medium, whereas the bacteriocin did not kill the S. mutans cell grown in a sucrose-containing medium [17]. The inhibitory mechanism of the bacterioci-like substance in this study may be different from that of other known bacteriocins.…”
Section: Discussioncontrasting
confidence: 55%
“…Differences in the sensitivity spectrum of the indicator strains were also noted among these three mutacins. Notwithstanding the differences in various properties, we now have strong evidence to indicate that bacteriocins, including mutacins, can affect microbial ecology in the oral flora and some bacteriocins may function to suppress caries development if they have the ability to inhibit the growth of mutans streptococci in vitro (Fitzgerald et al, 1986;Ikeda et al, 1982;Ooshima et al, 1985;Weerkamp et al, 1977).…”
Section: Discussionmentioning
confidence: 99%